2024
DOI: 10.3389/fphar.2024.1405163
|View full text |Cite
|
Sign up to set email alerts
|

Lobetyolin protects mice against LPS-induced sepsis by downregulating the production of inflammatory cytokines in macrophage

Zhonghua Chen,
Yixin Su,
Jingtong Ding
et al.

Abstract: Introduction: Sepsis is a clinical syndrome characterized by dysregulation of the host immune response due to infection, resulting in life-threatening organ damage. Despite active promotion and implementation of early preventative measures and bundle treatments, sepsis continues to exhibit high morbidity and mortality rates with no optimal pharmacological intervention available. Lobetyolin (LBT), the crucial component of polyacetylenes found in Codonopsis pilosula, has been scientifically proven to possess pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Interestingly, other articles have found that regulating cytokines and genes associated with immune responses to LPS can reduce the symptoms of LPS-induced sepsis in mice, which is consistent with our study. in addition, in KEGG analysis, samples can affect Transcriptional misregulation in cancer related genes ( Rosier et al, 2022 ; Chen et al, 2024 ) Our study showed that samples can reduce the secretion of pro-inflammatory cytokines in sepsis mice. Whether it is related to Transcriptional misregulation in cancer related genes still needs to be further explored ( Rawat et al, 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, other articles have found that regulating cytokines and genes associated with immune responses to LPS can reduce the symptoms of LPS-induced sepsis in mice, which is consistent with our study. in addition, in KEGG analysis, samples can affect Transcriptional misregulation in cancer related genes ( Rosier et al, 2022 ; Chen et al, 2024 ) Our study showed that samples can reduce the secretion of pro-inflammatory cytokines in sepsis mice. Whether it is related to Transcriptional misregulation in cancer related genes still needs to be further explored ( Rawat et al, 2021 ).…”
Section: Discussionmentioning
confidence: 76%